Booms and busts in house prices explained by constraints in housing supply - Narayan Bulusu; Jefferson Duarte; Carles Vergara-Alert (Bank of Canada, 2013)
We study the importance of supply constraints in explaining the heterogeneity in house price cycles across geographies in the United States. Comparing the equilibrium house price generated with and without supply constraints in a representative-agent model under irreversibility of housing investment, we derive a relationship between housing returns and changes in supply constraints and determinants of housing demand. Our empirical analysis shows that supply constraints play an important role in Metropolitan Statistical Areas (MSAs) with boom-and-bust behavior. We estimate that, in 19 of the largest MSAs in the United States, supply constraints contributed 25% to the dramatic rise in house prices from 2000 to 2006, and 17% to their sharp fall from 2006 to 2010.
Keywords: R310; 330; Asset Pricing; Economic models